Analisis Perilaku Generasi Milenial dalam Membayar Zakat di Era Digital (Studi Kasus Mahasiswa FEBI IAIN Kudus Angkatan 2019) (Jurnal Ekonomi dan Bisnis Islam, 2023)
This research aims to examine how the millennial generation pays zakat in the digital era. This type of research explains what happened in the field using a qualitative methodology followed by descriptive qualitative data analysis. Interviews, observations, and recording are the methods used in this study to obtain data. Two students from each study program at the Faculty of Economics and Business, IAIN Kudus in 2019 were used as research subjects with a total of 10 participants.The results of this study are the behavioral characteristics of the millennial generation in 2019 FEBI IAIN Kudus students in paying zakat fitrah still offline. In addition, there is the influence of online zakat knowledge, religiosity, transparency, income, and satisfaction which influence student preference decisions in paying zakat in the digital era. Knowledge of online zakat technology, transparency, and satisfaction greatly influence the preference decisions of FEBI IAIN Kudus Class of 2019 students in paying zakat in the digital era, religiosity and income affect the intention to pay zakat for 2019 FEBI IAIN Kudus Students. However, this does not affect the preference decisions of the millennial generation in paying zakat in the digital age.Keywords: Behavior, Zakat, Millennial Generation, Knowledge, Religiosity, Transparency, Income, Satisfaction.